Hidrodinâmica e transferência de oxigênio em três biorreatores Airlift de circulação interna geometricamente semelhantes - Cerri, Marcel Otávio (Universidade Federal de São Carlos, 2009)
Internal-loop airlift reactors (ALR) are a special class of pneumatic reactors. The use of this type of reactor has been attractive for chemical and biological reactions because of their simple construction without moving parts and low energy costs when compared with stirred tank reactors. In the present work, a study related to hydrodynamic and oxygen transfer in three geometrically similar scales of internal tube airlift bioreactors (2, 5, and 10 L) was conducted. The aim was to obtain useful information for further studies related to the scale-up of such reactor configuration. The gas hold-up, circulation time, mixing time, volumetric oxygen transfer coefficient, average shear rate, and mean bubble diameter of the air bubbles were evaluated in order to achieve a better comprehension of the hydrodynamic and mass transfer in airlift bioreactors. Values of gas hold-up and oxygen transfer were obtained for the three scales of ALR utilizing eight Newtonian and five non-Newtonian fluids. The superficial gas velocity and liquid viscosity had opposite effects with same order of magnitude. General correlations based on the dimensional analysis were proposed to relate global gas hold-up (ε) and volumetric oxygen transfer coefficient (kLa) to the geometrical parameters of the system, physical properties of the Newtonian and Non-Newtonian fluids, and superficial gas velocity. The correlations presented excellent fittings to the experimental data obtained for the three scales of ALR. The influence of the reactor internal diameter on the volumetric oxygen transfer coefficient was considered positive showing that in largerscale reactors an appropriate oxygen transfer can be reached under smaller aeration conditions. New methodologies to estimate the mean bubble size (dB) and average shear rate ( m γ& ) in the three scales of ALR were proposed. The semi-theoretical method to estimate dB was based on Higbie´s penetration theory using experimental data of ε and kLa. The methodology for evaluating the m γ& in ALRs was developed for non-Newtonian systems. The volumetric oxygen transfer coefficient was chosen as the appropriate characteristic parameter. The results of dB and m γ& obtained by the proposed methods are in agreement with the experimental values found in the literature. The effect of shear rate on clavulanic acid (CA) production by Streptomyces clavuligerus was examined both in a stirred tank bioreactor (STR) of 4 L and in an ALR of 6 L working volume, respectively, based on experimental data of the literature. Results showed that CA production was positively affected by shear conditions. In addition, the ALR presented values of m γ& higher than those found in a STR operated under the same oxygen transfer conditions.
Keywords: Engenharia bioquímica; Hidrodinâmica; Biorreator não convencional; Massa - transferência; Cisalhamento; Biorreatores pneumáticos; ENGENHARIAS::ENGENHARIA QUIMICA